Materiali per una didattica delle scritture pubbliche di cancelleria nell'Italia del Quattrocento - Lazzarini, Isabella (Scrineum, 2013)
This essay is an account of sources and “materials” chosen to offer a range of public written records produced and preserved by the late medieval Italian chancelleries, both in republics and principalities. It will examine three different groups of documents: first, the diplomatic sources, particularly the dispatches; then a group of administrative registers such as the libri officiorum; and finally the late medieval-early modern inventories of some public archives. The analysis focuses on the historical evolution as well as the possible homogeneity of these sources, trying to identify some links between political power and written records in late medieval Italy. As a matter of fact, the relationship between public written records, the forms of power and the documentary preservation both in past and in present times proves itself to be crucial in the process of transformation of the late medieval Italian states.